Effect of Acute Exercise on Cognitive Control (International Journal of Physiology, 2019)
AimTo assess effect of acute exercise on attention and memory (Cognitive Control).IntroductionStudies have shown that exercise and cognition are positively correlated. Cognitive control encompasses core cognitive process like inhibition, working memory and cognitive flexibility. Key elements like selection, scheduling and coordinated programming process are needed for cognitive control is brought about by target oriented, self-regulatory operations of brain. This study was specifically designed to assess effect of acute exercise on attention and memory (Cognitive Control) in fifty healthy young male subjects in the age group of 17–25 years.Material and MethodParticipant were instructed on methodology of Stroop colour Word Test, Ray Auditory Verbal Test and Complex figural test. Following instruction on methodology they were given five practice sessions. They were then divided in two group i.e. Group A had resting session on the second day and exercise session on the third day where as Group B had the session in exactly reverse order to that of group A.ResultAfter an acute session of exercise, the reaction time for Stroop colour condition, Stroop word condition and Strop colour word condition were decreased and this was found to statistically significant when compared to resting stage(before exercise). In case of backward digit span test and RAVLT total score, delayed recall and average recall no significant change was observed. The immediate recall time changed significantly after exercise.ConclusionA single bout of moderate intensity acute exercise has its effect on selective attention subset of cognitive control.